Multiscale damage evolution in polymer bonded sugar under dynamic loading. (November 2017) - Ravindran, Suraj; Tessema, Addis; Kidane, Addis
Highlights: Local deformation response of polymer bonded sugar under dynamic loading is studied experimentally at meso-scales. The fundamental mechanism that causes shear banding in polymer bonded explosive is investigated. The thermal softening due to plastic deformation, and mechanical softening due to damage accumulation, are responsible for hot spot formation. Abstract: Ultra-high-speed and high spatial resolution digital image correlation based experiments are performed to understand the sub grain level local failure mechanisms in polymer bonded explosives under dynamic loading. Polymer bonded sugar that mimics the mechanical properties of polymer bonded explosives is used in this study. The experiments are conducted in a split Hopkinson pressure bar setup at an intermediate strain rate. From the digital image correlation analyses, high strain localization was observed predominantly in the regions filled by the polymer binder surrounding the sugar crystals. The damage evolution was quantified by calculating the Poisson's ratio and volumetric strain as a function of loading. It was observed that the damage incubation is started at a very small global strain and causes mechanical softening in the material that leads to shear band formation. Also, the possible hotspot mechanism in the material was seen to be frictional heating of crystals and de-bonding of the polymer binder.